2013
DOI: 10.26719/2013.19.6.570
|View full text |Cite
|
Sign up to set email alerts
|

Injection practices among practitioners in private medical clinics of Karachi, Pakistan

Abstract: The aim of this study was to determine the frequency and determinants of sharps injuries among private health practitioners in slum areas of Karachi, Pakistan. All practitioners with at least 1 year of experience in a private medical clinic were asked to complete a self-administered, structured questionnaire (317/397 responded). Only 7.9% of practitioners were qualified from medical school, 12.3% were registered nurses and 8.8% lacked any professional qualifications. At least 1 sharps injury in the previous 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 15 publications
0
8
2
Order By: Relevance
“…18 In the present study 47% had needle stick injury only once which is higher than the study conducted by yousafzai et al (26.7%) and lower than study conducted by fullerton et al (75.6%). 16,19 In the present study 42% had 2-5 times in the last one year and which is lower than study conducted by fullerton et al (21.9%). 16 In the present study most of the participants had NSI while recapping the needle and similar finding was observed in the study conducted by Yousafzai et al and bayappa reddy N et al 17,19 In the present study the most common factor influenced NSI was hasty work and similar finding was observed in the study conducted by Bayappa Reddy N et al 17 In our study all private practitioners had heard of HIV post exposure prophylaxis (PEP) and almost similar finding was observed by Patricia A et al (98%).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…18 In the present study 47% had needle stick injury only once which is higher than the study conducted by yousafzai et al (26.7%) and lower than study conducted by fullerton et al (75.6%). 16,19 In the present study 42% had 2-5 times in the last one year and which is lower than study conducted by fullerton et al (21.9%). 16 In the present study most of the participants had NSI while recapping the needle and similar finding was observed in the study conducted by Yousafzai et al and bayappa reddy N et al 17,19 In the present study the most common factor influenced NSI was hasty work and similar finding was observed in the study conducted by Bayappa Reddy N et al 17 In our study all private practitioners had heard of HIV post exposure prophylaxis (PEP) and almost similar finding was observed by Patricia A et al (98%).…”
Section: Discussioncontrasting
confidence: 55%
“…16,19 In the present study 42% had 2-5 times in the last one year and which is lower than study conducted by fullerton et al (21.9%). 16 In the present study most of the participants had NSI while recapping the needle and similar finding was observed in the study conducted by Yousafzai et al and bayappa reddy N et al 17,19 In the present study the most common factor influenced NSI was hasty work and similar finding was observed in the study conducted by Bayappa Reddy N et al 17 In our study all private practitioners had heard of HIV post exposure prophylaxis (PEP) and almost similar finding was observed by Patricia A et al (98%). 18 Our study observation is higher than the other studies conducted by C Ooi et al (68%) and Biniam Mathewos et al (48%).…”
Section: Discussioncontrasting
confidence: 55%
“…21 On the other hand, a study conducted in Pakistan, found that 74.8% of HCWs administered injections with used syringes. 22 The current study showed that 41.9% of HCWs cleaned their hands with alcohol based hand rub before preparing an injection, 53% cleaned the patient's skin before the injection with an antiseptic, and protective gloves were used in 41.9% of observed injections. Similar findings was reported by Ain-Shams study, (44.2%, 30.9%, and 20.4% respectively).…”
Section: Discussionmentioning
confidence: 71%
“…In addition, high prevalence of HBV infections among the general population, lack of infection control activities, under-resourced health care system, and poor injection practices without any safety measures at first level care facilities in Pakistan further augment the risk of nosocomial transmission of HBV to HCWs. (10) The prevalence of hepatitis B surface antigen (HBsAg) positivity among Pakistani HCWs working at tertiary care hospitals has been studied by various authors. (11)(12)(13) The vaccination status of Pakistani primary HCWs has however not been studied before.…”
Section: Introductionmentioning
confidence: 99%